The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1103/physrevd.86.015007
|View full text |Cite
|
Sign up to set email alerts
|

Two Higgs bidoublet model with spontaneousPandCPviolation and decoupling limit to the two Higgs doublet model

Abstract: The two Higgs bi-doublet left-right symmetric model (2HBDM) as a simple extension of the minimal left-right symmetric model with a single Higgs bi-doublet is motivated to realize both spontaneous P and CP violation while consistent with the low energy phenomenology without significant fine tuning. By carefully investigating the Higgs potential of the model, we find that sizable CP-violating phases are allowed after the spontaneous symmetry breaking. The mass spectra of the extra scalars in the 2HBDM are signif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In a wide class of DM models, the DM particle χ can annihilate into the standard model (SM) particles through an s-channel resonance particle R. Such as the singlet scalar DM models [17][18][19][20][21][22][23][24][25][26] , the left-right symmetric models with extended stable scalar sectors [27][28][29][30][31][32][33][34] and the fermionic DM models [35][36][37][38][39][40][41]. The presence of the scalar R can also play an important role in electroweak phase transion [24,39,[42][43][44][45][46][47][48][49][50] and modify the interpretation of the DM-nuclei scattering [51,52].…”
Section: Introductionmentioning
confidence: 99%
“…In a wide class of DM models, the DM particle χ can annihilate into the standard model (SM) particles through an s-channel resonance particle R. Such as the singlet scalar DM models [17][18][19][20][21][22][23][24][25][26] , the left-right symmetric models with extended stable scalar sectors [27][28][29][30][31][32][33][34] and the fermionic DM models [35][36][37][38][39][40][41]. The presence of the scalar R can also play an important role in electroweak phase transion [24,39,[42][43][44][45][46][47][48][49][50] and modify the interpretation of the DM-nuclei scattering [51,52].…”
Section: Introductionmentioning
confidence: 99%
“…The Z 2 symmetry may be a residual symmetry from a global or local U (1). In the extension of the left-right symmetric models with a gauge singlet scalar, the Z 2 symmetry may originate from the parity and CP symmetries [27][28][29][30][31]. However, if EWPhT is also required, it was shown that the singlet scalar could contribute only up to 3% of the DM energy density [32,33].…”
Section: Introductionmentioning
confidence: 99%